Management: School With Dudi In Improving The Competence Of Graduates - Nangniva, Thantasia; Dermawan, Oki; Fauzan, Ahmad; junaidah, Junaidah (Journal of Advanced Islamic Educational Management, 2023)
This research aims to find out the planning, analyze organization, identify implementation, and evaluate cooperation with business and industry at State Vocational High School 7 Bandar Lampung in improving the competence of its graduates. Approach with descriptive qualitative method. Data collection with interview techniques, observation and documentation. Analyze the data by reducing data, displaying data and drawing conclusions. Test the validity of the data using triangulation techniques and sources. The results of this study indicate that SMKN 7 Bandar Lampung cooperation with the world of business and industry which begins with a planning that is carried out through survey and program analysis, preparation of partnership proposals, program preparation, organizing by detailing all the work that must be done. organizing by detailing all the work that must be done to achieve organizational goals, dividing the workload, and organizing the workload. organization, dividing the workload, and providing a mechanism for coordinating the work of organizational members. mechanism for coordinating the work of organizational members, implementation through curriculum validation, industry visits, internships, teacher or student training, vocational competency exams, practical equipment assistance, distribution of graduates through SWOT (strengths, weaknesses, opportunities, threats) and finally evaluation of each program with the business world and industry. program with the business world and industry which is carried out annually.